Material Based Penalty-Cost Quantification Model for Construction Projects Influencing Waste Management - Nawaz, Ahsan; Chen, Jian; Su, Xing; Zahid Hassan, Hafiz Muhammad (Frontiers in Environmental Science, 2022)
In recent decades, waste generation is a critical issue for the energy projects, which negatively affects the economy, environment, and society. This study estimates the penalty-cost based on the produced wastes in energy-infrastructure projects. Field survey & the BOQ data were collected from five mega projects. The difference of materials used and wastes generated between energy projects were evaluated statistically (ANOVA and Welch and Brown-Forsythe). A financial analysis was implemented for estimating the penalty cost. The study outcomes demonstrate that the amount of waste that project managers estimated is significantly lower than the actual amount generated. Furthermore, 0.055% of the total project cost of a penalty was estimated based on the waste produced at project sites. In the end, the estimated penalty was validated by comparing it with the six recent completed projects. The penalty calculated in this study could save the project cost and reduce the C&D waste influencing environmental policy & carbon emission.